Management oral care mengatasi mucositis pada pasien kanker yang menjalani terapi kemo dan radiasi: A systematic review - Siregar, Ngolu; Putri, Yosie Susanti Eka; Nuraini, Tuti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Oral mucositis (OM) is a common and highly symptomatic complication of cancer therapy that affects the quality of life function. Chemotherapy and radiation are the most widely used interventions in cancer treatment. The prevalence of oral mucositis side effects among 294 head and neck cancer patients was 93.9%. Purpose: To analyze oral care management to overcome mucositis in cancer patients undergoing chemotherapy and radiation therapy. Method: Literature review study using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and PICOS approach, P: cancer patients undergoing chemotherapy and radiation, I: oral care management, C: no specific treatment or other standard care, O: reducing severity and accelerating healing, S: randomized controlled trial (RCT). Literature search using keywords “management” AND